2000
DOI: 10.1093/milmed/165.8.579
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Improved Diabetic Management

Abstract: Effective control of diabetes is known to delay or prevent the end-organ complications of this disease. Can telemedicine improve a patient's ability to self-manage diabetes? Twenty-eight patients entered a study comparing home telemedicine consultation with standard outpatient care. A nurse case manager contacted the telemedicine group once a week under the direction of a primary care physician, who contacted the telemedicine group once a month. Laboratory studies and total body weight were measured at the beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 0 publications
1
129
0
3
Order By: Relevance
“…Communication with health care providers and health care facilities using telemedicine can improve diabetes care (21). Our findings of similar effects in the in-person and telemedicine groups support the necessity for larger studies to confirm this preliminary finding to enable Medicare, Medicaid, and third-party payers to determine policy for reimbursement for diabetes education services provided via telemedicine technology (22).…”
Section: Costs Of Telemedicine Interventionsupporting
confidence: 67%
“…Communication with health care providers and health care facilities using telemedicine can improve diabetes care (21). Our findings of similar effects in the in-person and telemedicine groups support the necessity for larger studies to confirm this preliminary finding to enable Medicare, Medicaid, and third-party payers to determine policy for reimbursement for diabetes education services provided via telemedicine technology (22).…”
Section: Costs Of Telemedicine Interventionsupporting
confidence: 67%
“…A reduction in HbA1c of 0.5 would be clinically meaningful [8]. The choice of 0.3 for the standard deviation of the mean difference was a logical guess, derived from the wide range of initial and follow-up values in the literature on diabetes management [9][10][11][12][13][14][15]. TWC experiences an average drop-out rate of patients who do not complete the entire four courses of 10-20% (K. Wiggins, personal communication, June 14, 2010).…”
Section: Study Design and Analysismentioning
confidence: 99%
“…Likewise, 14% of healthcare spending goes to treating it, amounting to hundreds of billions of dollars a year, and nearly 95% of diabetes cases are type 2 [6,7]. Lowering glycated hemoglobin (HbA1c) through disease management programs improve patient outcomes and with clinically significant benefits from even small reductions [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 18 studies identified involving synchronous interaction, most concern healthcare professionals such as nurses, dieticians, physiotherapists and others, interacting with patients for educational purposes. Some studies report on how home telemedicine consultations may replace standard outpatient care [22], where nurses are present at the home of the patients and a specialist participates through videoconferencing. Others report on outreach service delivery from a specialist hospital to regional clinics [23].…”
Section: Related Workmentioning
confidence: 99%